2016
DOI: 10.1007/s10549-016-3689-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular subtype profiling of invasive breast cancers weakly positive for estrogen receptor

Abstract: The estrogen receptor (ER) is a key predictive biomarker in the treatment of breast cancer. There is uncertainty regarding the use of hormonal therapy in the setting of weakly positive ER by immunohistochemistry (IHC). We report intrinsic subtype classification on a cohort of ER weakly positive early-stage breast cancers. Consecutive cases of breast cancer treated by primary surgical resection were retrospectively identified from 4 centers that engage in routine external proficiency testing for breast biomarke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 32 publications
2
37
0
2
Order By: Relevance
“…We based our current study on our previously published data in which we classified the intrinsic subtypes by PAM50 assay ( n = 55), with the addition of three new cases to this cohort. Applying the PAM50 assay showed that among the 58 weakly positive ER cases, 28 (48%) were assigned as basal‐like, 21 (36%) were classified as HER2‐enriched and only nine (16%) were classified as luminal subtype.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We based our current study on our previously published data in which we classified the intrinsic subtypes by PAM50 assay ( n = 55), with the addition of three new cases to this cohort. Applying the PAM50 assay showed that among the 58 weakly positive ER cases, 28 (48%) were assigned as basal‐like, 21 (36%) were classified as HER2‐enriched and only nine (16%) were classified as luminal subtype.…”
Section: Resultsmentioning
confidence: 99%
“…Weakly positive ER cases have also been reported by our group and others to be more clinically akin to ER‐negative than to ER strongly positive breast cancers, casting doubt on the current recommendations for diagnosis and treatment of this subgroup as a luminal subtype based on IHC assessment alone . Furthermore, the clinically problematic setting of weak ER positivity raises important questions about the benefit of hormonal therapies, with a missed opportunity to initiate more effective adjuvant treatments as chemotherapy …”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…In our institution, these are treated as ER negative disease, although some receive adjuvant endocrine therapy. Whether including these patients could skew our results is a legitimate question; however, molecular subtype analysis suggests that the majority of these cancers have the same profiles and clinical outcome as ER negative disease [72, 73]. …”
Section: Discussionmentioning
confidence: 99%